Kritik terhadap Konsep Ideologi Komunisme Karl Marx - Fadhillah Rachmawati (Jurnal Sosiologi Agama Indonesia (JSAI), 2020)
This article aims to analyse the ideological theory of communism by referring to the history of the early period of thought of Karl Marx and Frederick Engels. From a linguistic perspective, communism is a doctrine of liberating the proletariat to a classless society. In the following period, communism by Lenin, Stalin and Mao Zedong developed into a revolutionary movement and state leadership under the control of the communist party with individual cult theory. Communism has three basic concepts, namely: dialectics, historical materialism and classless. In conclusion, communism has historically evolved as a philosophy of life that emphasizes world materialism with its slogan ‘of each person according to ability, for each person as needed ‘and not just a political ideology that separates religious affairs from state affairs. So according to its nature, communism clearly denies the existence of the afterlife, even denying God in its applicative life. Therefore, the appropriate paradigm for criticizing this ideology is through a worldview approach, especially the Islamic worldview, because in this world is not only a material aspect but also a metaphysical aspect. By understanding that aspects of metaphysics, it can affect human social life, so they will better understand that God is who occupies the highest position in this nature.